2010
DOI: 10.1007/s10734-010-9327-5
|View full text |Cite
|
Sign up to set email alerts
|

Poststructural feminist pedagogy in English instruction of vocational-and-technical education

Abstract: The purpose of this study was to develop a poststructural feminist pedagogical model and to investigate whether vocational-and-technical college students receiving poststructural feminist instruction would exhibit better learning achievement and critical thinking ability, and express greater satisfaction with their classes than those receiving traditional instruction. In applying a poststructural feminist model, the researchers intended to help both the teacher and students work together to overcome the estran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Student Satisfaction Questionnaire (SSQ).-After the intervention, a 34item SSQ (Wang, Chao, & Liao, 2011) was administered using a 5-point rating scale with anchors 1: Strongly disagree and 5: Strongly agree to measure students' satisfaction toward the intervention in terms of learning objective, learning content and methods, instructor's qualities, learning environment, assessment, and overall. The range of possible scores was 34 to 170, and in a pilot study of 126 students the Cronbach's αs for the subscales and overall questionnaire were .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Student Satisfaction Questionnaire (SSQ).-After the intervention, a 34item SSQ (Wang, Chao, & Liao, 2011) was administered using a 5-point rating scale with anchors 1: Strongly disagree and 5: Strongly agree to measure students' satisfaction toward the intervention in terms of learning objective, learning content and methods, instructor's qualities, learning environment, assessment, and overall. The range of possible scores was 34 to 170, and in a pilot study of 126 students the Cronbach's αs for the subscales and overall questionnaire were .…”
Section: Methodsmentioning
confidence: 99%
“…A post-structural feminist pedagogical model (PFPM) allows students to use democratic dialogues to actively take control of the learning process and become empowered for knowledge construction (Wang, Chao, & Liao, 2011). Liao and Wang (2010) showed that both male and female students instructed under PFPM obtained higher English learning achievement, better critical thinking, and greater satisfaction, for they had more opportunities to speak their opinions without being criticized.…”
mentioning
confidence: 99%
“…Gender roles and class contribute to social support, expectations of women in vocational education, and women’s participation in male-dominated vocations. As discussed by Wang, Chao, and Liao (2011), applying feminist instruction can lead to all students’ enhanced performance in vocational education programs. Instruction styles are influential in students’ success and decision-making processes.…”
Section: Resultsmentioning
confidence: 99%
“…I do this as a personal choice; I prefer the use of it as a singular term to emphasise its contrast with other forms of pedagogy, and to underline the commonality of purpose of the various approaches it embraces. Many other authors have also opted for this singular terminology (Webb et al, 2002;Markowitz, 2006;Brown, 2009;Wang et al, 2011;Coia and Taylor, 2013;Light et al, 2015). Nevertheless, I stress that by using the singular term, I am not attempting to suppress the diversity of feminism or feminist pedagogy.…”
Section: Establishing a Feminist Classroommentioning
confidence: 99%
“…This was important because as Lawrence (2016) states, the wealth of USA literature on feminism and feminist pedagogy means it is easy to see work from the USA as the dominant narrative, but work from many other countries has also contributed to debate and enabled commonalities to be explored. For example, Wang et al, (2011) working in Taiwan discuss how a model of teaching based on poststructural feminist pedagogy had a positive effect on students' achievements and abilities to think critically.…”
Section: Establishing a Feminist Classroommentioning
confidence: 99%